Trouble in the Colonies: Review of D.W.A. Baker, Preacher Politician, Patriot: A life of John Dunmore Lang - B. Zuiddam (Acta Theologica)
From text: Some people write biographies of great men they admire for their particular virtues or achievements. Mr. Don Baker has a refreshing approach. He wrote a biography on the life of John Dunmore Lang not because he liked him, but because he did not. The preface introduces the reader to the kind of person he is: “A man to whom truth and falsehood come alike as he can best adapt them to his unmanly purposes.” The author uses this quote from one of Lang’s opponents at the time to characterise the subject of his biography.